Features of the digital transformation of the pharmaceutical business ("Journal "U". Economy. Management. Finance.", 2025)
In recent decades, technological progress has significantly changed many areas of life, and the pharmaceutical business is no exception. The article examines important areas of digitalization of business processes in the pharmaceutical industry, especially in conditions of economic instability. With the development of information technology, pharmaceutical companies began to implement various digital solutions, which improved information processing, management accounting and statistical data processing, as well as facilitated faster and more efficient information exchange, increased security and accuracy in coding and tracking medicines.In the article, the author gave a description of digital technologies introduced into the business processes of the pharmaceutical business, assessed the possibilities of digitalization for the business processes of the pharmaceutical business and proposed a methodology for evaluating the effectiveness of business processes of the pharmaceutical business, taking into account digitalization.
Keywords: digitalization; digital technologies; business processes; pharmaceutical business; business process assessment methods; promotion; business process efficiency